2014
DOI: 10.1021/ac4039652
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic “Deep Profiling”: An Enhanced Workflow to Reveal New Molecular Species of Signaling Lipids

Abstract: Current mass spectrometry-based lipidomics aims to comprehensively cover wide ranges of lipid classes. We introduce a strategy to capture phospho-monoester lipids and improve the detection of long-chain base phosphates (LCB-Ps, e.g., sphingosine-1-phosphate). Ten novel LCB-Ps (d18:2, t20:1, odd carbon forms) were discovered and characterized in tissues from human and mouse, as well in D. melanogaster and S. cerevisiae. These findings have immediate relevance for our understanding of sphingosine-1-phosphate bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 14 publications
1
66
0
Order By: Relevance
“…Menuz et al, were able to detect C17iso sphingosine-1-phosphate and also found a 10-fold increase in sphk-1 mutants [42]. Potentially novel sample preparation methods can overcome this limitation, which also enabled detection new forms of S1P in Drosophila [89]. Lastly, direct detection and identification of intact lipids using either shotgun or LC-MS based lipidomics will replace long isolation, derivatization and measurement of fatty acids and will lead to new insights.…”
Section: Challenges and Future Research Directionsmentioning
confidence: 99%
“…Menuz et al, were able to detect C17iso sphingosine-1-phosphate and also found a 10-fold increase in sphk-1 mutants [42]. Potentially novel sample preparation methods can overcome this limitation, which also enabled detection new forms of S1P in Drosophila [89]. Lastly, direct detection and identification of intact lipids using either shotgun or LC-MS based lipidomics will replace long isolation, derivatization and measurement of fatty acids and will lead to new insights.…”
Section: Challenges and Future Research Directionsmentioning
confidence: 99%
“…Wenk et al . have selectively extracted phospho-monoester lipids by an imidazolium polymer, and after derivatization with trimethylsilyldiazomethane (TMS-diazomethane), they successfully determined the long-chain base phosphates (LCB-Ps, e.g., sphingosine-1-phosphate) [29]. Moreover, this is particularly effective for selectively extracting some lipids on the basis of their discrepancy in the adsorption capability on solid phase extraction columns through different eluents [30,31,32].…”
Section: The Methods For Lipid Extractionmentioning
confidence: 99%
“…The quantification of S1P is challenging due to its zwitterion character, even more so the determination of relatively low levels in a complex matrix of other lipids. Presently, the most used detection methods are based on HPLC separation of fluorescently modified S1P [23,24] and LC-MS/MS procedures [25,26]. In addition to the analytical challenge, the origin of S1P in plasma samples and its stability during sample storage warrant special attention.…”
Section: Introductionmentioning
confidence: 99%